Design and Quality for Biomedical Technologies XI 2018
DOI: 10.1117/12.2287854
|View full text |Cite
|
Sign up to set email alerts
|

An applicable approach for extracting human heart rate and oxygen saturation during physical movements using a multi-wavelength illumination optoelectronic sensor system

Abstract: applicable approach for extracting human heart rate and oxygen saturation during physical movements using a multi-wavelength illumination optoelectronic sensor system," Proc. SPIE 10486, Design and Quality for Biomedical Technologies XI, 104860S (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Developments into multi-wavelength PPG sensing hardware has seen dramatic improvements of the past decade in research settings. Initial hardware was reliant on fiber optics [41], [68] which then progressed into Optical Electronic Patch Sensor (OEPS) development [51], [69] due to its low cost and simple form factor with researchers also exploring earworn, finger-worn, forehead-worn and wrist-worn PPG sensors [57], [70]- [72]. The latest development in hardware for multiwavelength PPG sensing is an on-chip spectrometer approach based on plasmonic filters [73] which has been adapted for an all-wavelength PPG sensing device [74].…”
Section: A Multi-wavelength Ppg Research Hardwarementioning
confidence: 99%
See 2 more Smart Citations
“…Developments into multi-wavelength PPG sensing hardware has seen dramatic improvements of the past decade in research settings. Initial hardware was reliant on fiber optics [41], [68] which then progressed into Optical Electronic Patch Sensor (OEPS) development [51], [69] due to its low cost and simple form factor with researchers also exploring earworn, finger-worn, forehead-worn and wrist-worn PPG sensors [57], [70]- [72]. The latest development in hardware for multiwavelength PPG sensing is an on-chip spectrometer approach based on plasmonic filters [73] which has been adapted for an all-wavelength PPG sensing device [74].…”
Section: A Multi-wavelength Ppg Research Hardwarementioning
confidence: 99%
“…Motion artifacts can be classified as either periodic or non-periodic and can possess amplitudes much larger than the pulsatile component of the signal [72], [116]. Blanos et al showed that green (525nm) and orange (590nm) light were affected by artifacts from motion to a lesser degree than red light (650nm) [69]. Matsumura et al agreed stating that the signal to noise ratio (SNR) for green (530nm) and blue (470nm) light was higher than red (640nm) when being subject to various motion types [110].…”
Section: Multi-wavelength Ppg Motion Artifact Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements performed with green light (525 nm) and blue light (470 nm) shown the best agreement in terms of earth rate with synchronised ECG ambulatory measurements [18]. In a similar approach, by using a multi-spectral PPG device during physical activities, Blanos et al [19] demonstrated that green light features highest agreement with simultaneous ECG recording (with a bias of 0.1261 BPM and standard deviation of 1.244 BPM). Using multiple wavelength laser sources and associated wide-band spectrometer, Spigulis et al [16] evaluated differences in PPG waveform shape.…”
Section: Parametersmentioning
confidence: 99%
“…The aim of the study is to research how to effectively work out SpO2 by means of mOEPS with its unique multi-wavelength illumination functionality. As the mOEPS has four wavelengths, e.g., green (525 nm), orange (595 nm), red (650 nm) and near Infrared (IR) (870 nm), the green and orange illuminations were used as primarily results to extract SpO2 [23]. The study was specified to be able to operate under a number of different scenarios including physical movements [24].…”
Section: Introductionmentioning
confidence: 99%